Goniopolarimetric Properties of Typical Satellite Material Surfaces: Intercomparison with Semi-Empirical pBRDF Modeled Results - Min Yang; Hongxia Mao; Jun Wu; Chong Zheng; Li Wang (Photonics)
Light reflected from satellite surfaces is polarized light, which plays a crucial role in space target identification and remote sensing. To deepen our understanding of the polarized reflectance property for satellite material surface, we present the experiments of polarimetric laboratory measurements from two typical satellite materials in the wavelength range of 400–1000 nm by using a goniometer instrument. The bidirectional polarized reflectance factor (BPRF) is used to describe the polarization characteristics of our samples. The polarized spectral reflectance and distribution of BPRF for our datasets are analyzed. Furthermore, five semi-empirical polarized bidirectional reflectance distribution functions (pBRDFs) models for polarized reflectance of typical satellite material surfaces (Preist–Germer model, Maxwell–Beard model, three-component model, Cook–Torrance model, and Kubelka–Munk model) are quantitatively intercompared using the measured BPRFs. The results suggest that the measured BPRFs of our samples are spectrally irrelevant, and the hemispherical distribution of BPRFs is obviously anisotropic. Except for the Preist–Germer model, the other semi-empirical models are in good agreement with the measured BPRF at the selected wavelengths, indicating that we can accurately simulate the polarized reflectance property of the satellite surface by using the existing polarimetric models. The Kubelka–Munk pBRDF model best fits the silver polyimide film and white coating surfaces with RMSE equal to 3.25% and 2.03%, and the correlation coefficient is 0.994 and 0.984, respectively. This study can be applied to provide an accurate pBRDF model for space object scene simulation and has great potential for polarization remote sensing.